MENGHUBUNGKAN INOVASI DAN MASYARAKAT: PENGEMBANGAN E-MARKETPLACE PKM UNIVERSITAS TERBUKA - Prakoso, Teguh; Nursantoso, Teguh; Permanasari, Devi; Rovandi, Harris; Mustari, Mustari; Heriani, Heriani; Lase, Sepandil Laras (LPPM Universitas Bina Bangsa, 2025)
Community Service (PkM) is one of the pillars in the tridharma of higher education which aims to provide a real impact on society. This study develops an e-marketplace application